Permainan Alat Musik dalam Mengembangkan Aspek Bahasa Anak Usia Dini: Musical Instrument Games in Developing Early Childhood Language Aspects - Yuliantika , Nanda; Nurafiza, Sammania; Turrahmah, Nadia; Anggraini, Adelia (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2022)
The problem of this research was children low language ability development. The objective of this research was to find out the correlation between role playing and children language ability in group B. Research used quantitative correlational methode. This research was conducted in Al-Hidayah kindergarten school in Kalirejo Lampung with population of 81 children. The 30 respondent were taken by using purposive sampling technique. Data were collected by observations and documentations and analyzed by using Spearman’s Rank correlation technique. The result showed that there was a correlation between role playing and children language ability development.